Symposium 1: Problematising Participatory Research for Developing Semantic Web Technologies - Tracy, Frances (Proceedings of the International Conference on Networked Learning, 2016)
This paper contributes to a symposium on ‘Designs for learning with the Semantic Web (Web 3.0)’ by presenting the outcomes of critical reflection on methodological issues relating to the design of semantic web technologies for networked learning. Semantic web technologies show great potential for supporting networked learning but are unsettled and under-researched in educational contexts, thus classed within this symposium as ‘emergent’. The design of this emergent and complex technology is considered in relation to empirical research data from an interdisciplinary, multi-institutional technology enhanced learning (TEL) research project. The research project explored the potential of semantic web technologies in Higher Education (HE) to support the use of cases in teaching and learning. Data was collected throughout the project including researcher's wiki-based reflective research logs, transcripts from project meetings and interviews and focus groups with participants and observation notes. Critical reflection on the research process was supported through engagement with this data, which allowed the recognition of nondeterministic constructs and fluidity and contingency in research practice. Therefore, this paper problematises participation by highlighting uncertainties and contingencies inherent in the enactment of participatory research methodology. Rather than viewing uncertainty and contingency as devaluing research, the case is made that this can allow for enrichment of the development process and subsequently the research outcomes. The flexible and emergent nature of semantic web technology matched with participatory approaches in the design of emergent technologies allows for reflection, adaptation and flexible action relating to pedagogy and practices which is essential in educational contexts that are rapidly changing. The findings highlight the uncertain and contingent nature of (1) the settings where design took place; (2) acceptance or rejection of research methods; and (3) the community groups that emerged as interested parties in our work. Vignettes from two different research settings are used to show how participation was enacted reflectively and responsively leading to some positive outcomes; including the development of new teaching practices and new technologies, which were fed back into the open source development of educational semantic web technologies. Therefore, researchers in the field of networked learning are encouraged to ‘design with participatory research’ to match the challenges posed by complex and emergent technologies and changeable educational contexts rather than attempting to apply standardised forms of design methodologies.